Plastic strain localization induced by microstructural gradient in laser cladding repaired structures. (June 2020) - Guévenoux, Camille; Hallais, Simon; Balit, Yanis; Charles, Alexandre; Charkaluk, Eric; Constantinescu, Andrei
Graphical abstract: Highlights: Characterization of microstructural gradient in laser cladding repaired specimen. Observation of plastic strain at the grain scale with Digital Image Correlation. Identification of strain localization pattern in the repaired specimen. Investigation of the role of grain size effect in the reported strain distribution. Abstract: Laser Cladding is an additive manufacturing technology well suited for the repair of complex metallic components. The repair is a two-step process: first, one removes the worn region and then, the initial geometry is reconstructed locally. The aim of this work is to study the influence of the microstructural gradient on the strain localization in repaired structures. More precisely, we perform in-situ SEM tensile tests completed by EBSD observations of the microstructure in the interface neighborhood between the base material and the repaired region. Furthermore, we monitor the evolution of the local plastic strain distribution at the grain level until failure. This is performed by Digital Image Correlation methods and superposition of grains contours and strain maps. The observations of grain size and plasticity are compared with predictions provided by a Hall-Petch model. The study emphasizes the importance of the microstructural gradient in the vicinity of reparation interface, more precisely it reveals that this gradient induce multiaxial strains and that the strain localization phenomenon is governed mainly by a grain size effect.